Electrode material, cathode foil for electrolytic capacitor, and electrolytic capacitor

The cathode foil structure with a metal-containing first layer and carbon second layer on a smooth base material improves adhesion and resistance, reducing ESR and enhancing durability in electrolytic capacitors.

JP2025012894AActive Publication Date: 2025-01-24JAPAN CAPACITOR IND CO LTD

Patent Information

Application Number
JP2023116068
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-24
Estimated Expiration
2043-07-14

AI Technical Summary

Technical Problem

Existing electrolytic capacitors face issues with adhesion to solid electrolytes, high interface resistance, chemical resistance, and durability problems due to chemical polymerization and moisture, along with high ESR and limited frequency range, especially in hybrid and solid electrolytic capacitors.

Method used

A cathode foil structure with a smooth base material having an oxide layer and an inorganic conductive layer with a first conductive layer containing metal and/or metal compounds and a second conductive layer of carbon, featuring an uneven surface and a mixed layer, optimized for adhesion and resistance through XPS and Raman spectroscopy analysis.

Benefits of technology

The solution enhances adhesion, reduces ESR, improves chemical resistance and durability, and maintains low capacity while allowing for a wider frequency range, addressing the limitations of existing capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012894000001_ABST
    Figure 2025012894000001_ABST
Patent Text Reader

Abstract

To realize an electrode material and the like which can be used in a cathode foil for an electrolytic capacitor and the like and solve at least one problem regarding: the adhesiveness to a solid electrolyte; the contact resistance on a boundary surface; a property of holding a solid electrolyte and an electrolytic solution; the deterioration resistance with respect to a solid electrolyte, an electrolytic solution, and moisture; a capacitive component (a synthetic capacitance is not exhibited or is low); thinning; low cost; and winding deviation.SOLUTION: An electrode material is provided which comprises, on a smooth substrate, an oxide layer, a first conductive layer, a mixed layer, and a second conductive layer in this order. The first conductive layer has convex and concave portions on a front side and contains a metal and / or a metal compound. The second conductive layer contains carbon. In the mixed layer, the material constituting the first conductive layer and the material constituting the second conductive layer are mixed. Bonding between carbon atoms and the metal element atoms forming the first conductive layer accounts for at least 5%. The electrode material has a surface area enhancement factor of at least 6.5, based on the maximum current value in the cyclic voltammogram. The full width at half maximum of the G-band peak of the carbon in the second conductive layer is at least 3.8 times that of graphite crystals.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode material, in particular to a cathode foil for an electrolytic capacitor that can be used in electrolytic capacitors such as solid electrolytic capacitors and hybrid capacitors, and to an electrolytic capacitor. [Background technology]

[0002] The functions and characteristics required for the cathode of a hybrid capacitor are as follows: (i) It has good adhesion to the solid electrolyte and has low contact resistance at the interface. (ii) A solid electrolyte, which has a layer (geometric structure and surface modification) to hold the electrolyte. (iii) Resistance to degradation caused by solid electrolytes, chemical polymerization solutions, electrolytes, and moisture. (iv) It has no capacitance or has a low capacitance and behaves as a low resistance conductor. (v) Thinning is feasible. (vi) Low cost. Among the above (ii) and (iii), except for compatibility with the electrolyte, these can be said to be extremely important functions and characteristics for the cathode of a solid electrolytic capacitor.

[0003] In this regard, for example, a foil in which a smooth titanium layer is applied to a smooth foil and a smooth carbon layer is applied thereon has insufficient adhesion to the solid electrolyte dispersion in an aqueous solution (i), and poor retention of the electrolyte (ii). In particular, it is difficult to maintain a healthy doped state for a solid electrolyte made of a conductive polymer, resulting in high resistance when made into an element. Chemically etched cathode foils are difficult to miniaturize due to their thick foil thickness, and when combined with an anode to make a capacitor, a composite capacitance is generated, resulting in a low capacity extraction rate of the anode. In addition, while the ESR (Equivalent Series Resistance) is low on the high frequency side such as 100 kHz, the ESR is extremely high on the low frequency side such as 120 Hz, and the frequency range in which the ESR is low is narrow. The contact resistance with the solid electrolyte is high, and the parts not covered with the solid electrolyte depend on the electrolyte, so there is concern about low-temperature characteristics. Furthermore, there is a risk that the cathode foil may be locally chemically converted during the aging anodization process after the element formation, which may result in a decrease in capacity and an increase in resistance. For example, the chemical conversion coating layer applied to the aluminum substrate has a certain degree of protection against the electrolyte. However, it is difficult to completely prevent chemical reactions between the chemical polymerization solution and the acid electrolyte used to maintain the doped state of the solid electrolyte, and between the substrate and the traces of moisture, etc., for solid electrolytes made of conductive polymers. On the other hand, if the natural oxide coating or chemical conversion coating comes into direct contact with the solid electrolyte in its original state, a depletion layer will be generated at the contact interface, resulting in high contact resistance.

[0004] In foils that have been given a chemically etched foil, an intermediate layer (titanium layer), and a carbon layer, the foil is thin and the etched layer can hold the conductive polymer and electrolyte, but it is difficult to completely coat the inside of the etched layer with the titanium layer or carbon layer given on the etched layer, and an aluminum oxide layer is required to protect it from electrolyte, solid electrolyte, and chemical polymerization chemicals (for example, a chemically coated film of about several volts is required). This chemically coated film layer also has the function of protecting it from electrolyte, as mentioned above, but it also behaves as an insulator if left as is, and is likely to cause high resistance. It can be said that many of these problems also apply to solid electrolytic capacitors that do not use electrolyte and use only solid electrolytes.

[0005] Various cathode foils have been developed for use in electrolytic capacitors such as solid electrolytic capacitors and hybrid capacitors. Patent documents 1 and 3 describe electrolytic capacitors in which an inorganic conductive layer is formed on the surface of a cathode foil that has been roughened by etching (surface expansion ratio 1.5 to 500 times). However, these cathode foils have the following problems: When using an etched base material in which a smooth base material has been enlarged by etching, it is difficult for the inorganic conductive layer material to reach the inside of the etched layer, and it is difficult to completely cover the inside of the etched layer with the inorganic conductive layer material, so there will be areas where the aluminum, a component of the base material, is exposed. The exposed aluminum surface has a coating of aluminum oxide, which is an insulator and therefore has high resistance. Exposed aluminum has poor chemical resistance and has problems with durability against polymers and electrolytes. Since the base material is dissolved by etching, there are significant issues with regard to handling strength, thin foil production, residual chlorine, waste liquid treatment, and manufacturing costs. There are problems such as:

[0006] Patent Document 4 describes a cathode foil for an aluminum electrolytic capacitor, which is characterized in that a first layer made of at least one of a metal and its nitride, carbide, carbonitride, and oxide is formed on the surface of an aluminum foil, and a second layer made of at least one of a metal and its nitride, carbide, carbonitride, and oxide is formed on the first layer, and the first layer has a denser structure than the second layer. However, the invention described in Patent Document 4 is mainly aimed at improving hydration resistance as a cathode for a capacitor that uses only an electrolyte solution containing water as an electrolyte, and there is room for improvement in reducing resistance and improving durability of a cathode that can be used in electrolytic capacitors such as hybrid capacitors and solid electrolytic capacitors.

[0007] Patent Document 2 describes a cathode foil for a hybrid capacitor in which a smooth substrate is used and a carbon layer is formed thereon. Patent Document 5 describes a cathode foil for a solid electrolytic capacitor in which a smooth substrate is used and carbon exists on a metal layer. However, since the surface layer of these cathode foils does not have uneven parts, it is considered that there is room for further improvement in ESR and durability. In addition, since the surface layer of the cathode foil does not have uneven parts, the frictional force with the separator paper (isolation paper) is weak, and when the winding core jig is pulled out during the element winding process of the electrolytic capacitor, the cathode foil is likely to jump out in the direction of pulling out the winding core jig, resulting in winding misalignment.

[0008] Patent Document 9 describes an electrolytic capacitor that uses a cathode containing a plurality of metal particles with a median diameter of about 20 to about 500 micrometers that are arranged on the surface of a substrate and sintered together, but the size in microns is too large to obtain the geometric structure required to hold the solid electrolyte and electrolyte solution, and there is room for improvement.Other conventional techniques include Patent Documents 6 to 8 and 10 to 24, but it is believed that there is room for improvement in function and performance in all of them. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2016 / 174806 [Patent Document 2] International Publication No. 2016 / 174807 [Patent Document 3] International Publication No. 2016 / 189779 [Patent Document 4] JP 2014-022707 A [Patent Document 5] JP 2012-174865 A [Patent Document 6] JP 2023-002273 A [Patent Document 7] International Publication No. 2017 / 090241 [Patent Document 8] JP 2019-179884 A [Patent Document 9] JP 2007-243203 A [Patent Document 10] JP 2015-073015 A [Patent Document 11] JP 2019-179884 A [Patent Document 12] U.S. Pat. No. 1,089,6783 [Patent Document 13] International Publication No. 2021 / 107063 [Patent Document 14] International Publication No. 2012 / 115050 [Patent Document 15] JP 2004-281223 A [Patent Document 16] JP 2012-195527 A [Patent Document 17] JP 2011-192924 A [Patent Document 18] Patent Publication No. 2021-145135 [Patent Document 19] US Patent Application Publication No. 2009 / 0161299 [Patent Document 20] European Patent Application Publication No. 3817020 [Patent Document 21] US Patent Application Publication No. 2014 / 0036416 [Patent Document 22] US Patent Application Publication No. 2021 / 0383981 [Patent Document 23] JP 2005-294500 A [Patent Document 24] International Publication No. 2010 / 029598 [Patent Document 25] JP 2006-190878 A [Patent Document 26] Patent Publication No. 2022-057601 [Patent Document 27] Patent Publication No. 2022-057985 Summary of the Invention [Problem to be solved by the invention]

[0010] In view of the above, the present invention provides the following (1) to (7): (1) It has good adhesion with the solid electrolyte and has low contact resistance at the interface. (2) Having a solid electrolyte, a layer (geometric structure and surface modification) for retaining the electrolyte. (3) Excellent resistance to deterioration caused by solid electrolytes, chemical polymerization solutions, electrolytic solutions, and moisture. (4) It has no capacitance or has a low capacitance and behaves as a low-resistance conductor. (5) It is possible to make the material thinner. (6) Low cost. (7) It is difficult for the winding to become misaligned. The present invention aims to provide an electrode material that has at least one of the above advantages and can be used for a cathode foil for an electrolytic capacitor, or an electrolytic capacitor that has a cathode foil using such an electrode material. [Means for solving the problem]

[0011] In order to solve the above problems, the present invention provides a conductive film having an oxide layer on a smooth substrate, and further having an inorganic conductive layer on the oxide layer, the inorganic conductive layer having a first conductive layer containing a metal and / or a metal compound and a second conductive layer containing carbon, the first conductive layer having an uneven portion on its surface side, the second conductive layer being located on the outermost layer of the inorganic conductive layer, a mixed layer being formed between the first conductive layer and the second conductive layer, in which a substance constituting the first conductive layer and a substance constituting the second conductive layer are mixed, and the components of the mixed layer are substantially the same as those of the substance constituting the first conductive layer. An electrode material configured to change from a component containing only a substance constituting the second conductive layer to a component containing substantially only a substance constituting the second conductive layer from the first conductive layer to the second conductive layer, wherein when the abundance of each C bond state is analyzed in the depth direction from the surface layer of the second conductive layer by XPS (X-ray photoelectron spectroscopy), the ratio of the abundance of bonds between atoms of metal elements constituting the first conductive layer and carbon atoms to the total abundance of each C bond state by C1s spectrum is 5% or more, and the sweep range is ±0.3V vs Pt, and the sweep speed is 500mV / sec. The electrode material provides an electrode material in which the maximum current value of a cyclic voltammogram obtained by cyclic voltammetry under the conditions of an electrolyte at 30°C, a Pt reference electrode, a stainless steel counter electrode, and a working electrode as electrode materials is 6.5 times or more of the maximum current value of a cyclic voltammogram obtained under the conditions of a smooth substrate as the working electrode, and in which the half width of the G band peak obtained by peak separation in a Raman spectrum by Raman spectroscopy is the half width of the carbon contained in the second conductive layer is 3.8 times or more of the half width of crystalline graphite.

[0012] The "smooth substrate" here is, in one example, a substrate that has not been subjected to a roughening treatment such as etching, but the substrate surface does not need to be completely flat. The smooth substrate also includes those having minute roughness or undulations on the surface due to unavoidable rolling streaks or scars that occur slightly during the foil manufacturing process such as rolling (naturally, the substrate surface may be completely smooth). The "oxide layer" may be an oxide layer formed without any special treatment, such as a natural oxide coating, or an oxide layer formed intentionally by a treatment such as a chemical conversion treatment. The oxide layer may completely cover the smooth substrate, or may cover only a part of it, or the smooth substrate and the first conductive layer may be in direct contact with each other, for example, by the material of the dense layer of the first conductive layer penetrating the oxide layer (forming the dense layer by the arc ion plating (AIP) method, etc., described later). Furthermore, when the mixed layer and the second conductive layer are formed on the uneven portion of the first conductive layer, the mixed layer and the second conductive layer may be divided into multiple parts due to the shape of the uneven portion (see FIG. 1 for the embodiment described later), but the "layer" in the above description and the following description may be a "layer" formed in such a manner by dividing into multiple parts (this is true not only for the mixed layer and the second conductive layer, but also for any layer). In addition, as described later, "including substantially only the substance constituting the first conductive layer" and "including only the substance constituting the first conductive layer" do not necessarily mean that no components other than the "substance constituting the first conductive layer" are included, and "including substantially only the substance constituting the second conductive layer" and "including only the substance constituting the second conductive layer" do not necessarily mean that no components other than the "substance constituting the second conductive layer" are included (other components may be included within a range in which the function of the electrode material is maintained to an acceptable degree). Furthermore, in the above description, "changing from a component containing substantially only the material constituting the first conductive layer to a component containing substantially only the material constituting the second conductive layer as one moves from the first conductive layer to the second conductive layer" does not necessarily mean that the content of the material constituting the second conductive layer in the mixed layer increases monotonically in the direction from the first conductive layer to the second conductive layer.The actual components at each position in the mixed layer may vary depending on the variation in the concentration of each component caused by the limitations of manufacturing technology, etc. However, preferably, the mixed layer is formed so that the content of the material constituting the second conductive layer increases continuously from the first conductive layer toward the second conductive layer.

[0013] The material constituting the first conductive layer and the material constituting the second conductive layer may be different from each other.

[0014] The smooth substrate and the first conductive layer may be composed of different materials.

[0015] The second conductive layer may be a layer consisting essentially of carbon.

[0016] In the above description, "consists essentially of carbon" or "consists of carbon" does not necessarily mean that the second conductive layer does not contain any components other than carbon as a material constituting the layer. The actual composition of the components may vary depending on the control of component purity within the layer, the limitations of manufacturing technology regarding the inclusion of impurities, and the degree of resistance as an allowable error for the electrode material in individual products (the second conductive layer may contain components other than carbon as long as the function of the electrode material is maintained to an allowable degree). The same applies to descriptions such as "consists essentially of", "consists of", "consists essentially of only", and "contains only".

[0017] The inorganic conductive layer may further have a dense layer in which metals and / or metal compounds are densely present, and the dense layer may be formed between the oxide layer and the first conductive layer. Note that "densely present" here means that (metals and / or metal compounds) are densely present compared to the "uneven portion" described above.

[0018] Both the first and second conductive layers of the inorganic conductive layer, or at least the first conductive layer, may be layers made of particle deposition layers, and the first conductive layer may be a layer containing at least one of titanium, aluminum, and their nitrides, oxides, oxynitrides, carbides, and carbonitrides. Although the materials that can be used for the first conductive layer are not limited to these, when an aluminum substrate is used as the substrate, it is preferable to use metals such as titanium (Ti) and aluminum (Al) from the viewpoints of energy efficiency and adhesion to the aluminum substrate (including alloys containing multiple components, as long as the adhesion to the substrate and the conductivity of the first conductive layer are not impaired).

[0019] The oxide layer may be a phosphorus-containing oxide layer.

[0020] The smooth substrate may be a substrate containing aluminum or an aluminum alloy. Note that the material that can be used as the substrate is not limited to aluminum, and any other material such as valve metals tantalum (Ta), titanium (Ti), niobium (Nb), hafnium (Hf), zirconium (Zr), zinc (Zn), tungsten (W), etc., or an aluminum alloy to which any of these materials is added may also be used.

[0021] The carbon may be graphite-like carbon.

[0022] There is no particular restriction on the type of material to be used as carbon, but graphite-like carbon, which has particularly excellent electrical conductivity among carbon materials, is preferable in terms of reducing the ESR of the electrolytic capacitor. It is also preferable in terms of manufacturing costs. Here, graphite-like carbon is a material that has diamond bonds (sp 3 Hybrid orbital bonds) and graphite bonds (carbon-carbon sp 2This refers to carbon that has an amorphous structure in which both bonds (sp 2 and sp 3) are mixed, and in which the proportion of graphite bonds exceeds 50% (the number of graphite bonds is greater than the number of diamond bonds). However, in addition to the amorphous structure, it also refers to carbon that has a crystalline structure that is partially composed of graphite structures (i.e., sp 2 and sp 3). 2 This also includes those that have a phase consisting of a hexagonal crystal structure with hybrid orbital bonds. 3 Bonds and sp 2 The proportion of the bond state can be analyzed by Raman spectroscopy or XPS (X-ray photoelectron spectroscopy, also known as ESCA).

[0023] The BET specific surface area using krypton (Kr) as the adsorption gas may be 1.5 times or more the BET specific surface area of ​​the smooth substrate.

[0024] The BET specific surface area using krypton (Kr) as the adsorption gas may be 1.5 times or more the BET specific surface area of ​​the smooth substrate, and the average diameter of the projections of the uneven portion on the surface side of the inorganic conductive layer may be 210 nm or less.

[0025] In the electrode material provided by the present invention, the static friction coefficient and kinetic friction coefficient of the surface on the surface side against the separator paper may be higher than the static friction coefficient and kinetic friction coefficient of the surface on the surface side against the separator paper of an electrode material having a conductive layer that is the outermost layer on the surface side and is made of carbon on a smooth base material and has no uneven portion on the surface side.

[0026] The present invention also provides a cathode foil for an electrolytic capacitor, in which at least a solid electrolyte is interposed between an anode foil and a cathode foil, the cathode foil using the above-mentioned electrode material of the present invention.

[0027] The present invention also provides an electrolytic capacitor having at least a solid electrolyte between an anode foil and a cathode foil, the electrolytic capacitor including the cathode foil of the present invention described above. In one example, a solid electrolytic capacitor is provided.

[0028] The electrolytic capacitor may be an electrolytic capacitor in which an electrolyte is further interposed between the anode foil and the cathode foil. In one example, a hybrid capacitor is provided. Effect of the Invention

[0029] The present invention provides an electrode material that can be used for a cathode foil for an electrolytic capacitor and has at least one of the advantages (1) to (7) listed above with respect to the problems to be solved by the invention, or an electrolytic capacitor that includes a cathode foil using such an electrode material. By using a smooth foil instead of an etched substrate, there is no need to worry about residual chlorine, and there is no problem with exposed aluminum due to the difficulty of the inorganic conductive layer material penetrating into the etched layer. This makes it possible to improve resistance to deterioration (chemical resistance and durability) against solid electrolytes, chemical polymerization solutions, electrolytic solutions and moisture (3), makes it possible to make the product thinner while maintaining its strength (5), and furthermore, by eliminating the etching process, it is possible to reduce costs, including the problem of wastewater facilities (6). By applying an inorganic conductive layer with a rough surface, for example by vapor deposition, to a smooth foil, it is possible to have a layer with a geometric structure suitable for holding a solid electrolyte and an electrolyte solution (2). The geometrical uneven structure applied to the surface layer improves adhesion to the solid electrolyte (1). Furthermore, by setting the maximum current value of a cyclic voltammogram obtained under specified conditions using the working electrode as an electrode material to be 6.5 times or more the maximum current value when the working electrode is a smooth substrate, the ESR reduction effect is achieved by improving the retention of the solid electrolyte and the electrolyte solution. (1 and 2) The geometric unevenness applied to the surface layer increases the static and dynamic friction (friction coefficients) with the separator paper, preventing misalignment, which is prone to occur when the winding core jig is removed during the element winding process for electrolytic capacitors (7). By providing a layer containing carbon as the outermost layer of the inorganic conductive layer, it is possible to produce a cathode foil with low resistance and no capacitance component. (The generation of a depletion layer due to contact between the solid electrolyte and, for example, an aluminum oxide film is suppressed by forming a first conductive layer containing a metal and / or a metal compound and a second conductive layer containing carbon on the aluminum oxide layer, thereby significantly reducing the contact resistance with the solid electrolyte) ((1) and (4)). Regarding the half-width of the G-band peak obtained by peak separation in the Raman spectrum using Raman spectroscopy, by making the half-width of the carbon contained in the second conductive layer 3.8 times or more the half-width of the crystalline graphite, the deterioration resistance (chemical resistance and durability) to solid electrolytes, chemical polymerization solutions, electrolyte solutions and moisture is improved ((3)). By forming a mixed layer with chemical bonds between the first conductive layer and the second conductive layer containing carbon, and making the amount of bonds between the atoms of the metal elements and carbon atoms that make up the first conductive layer 5% or more of the total amount of each C bond state as determined by XPS analysis, the electrode material becomes a low-resistance conductor (4). [Brief description of the drawings]

[0030] [Figure 1] FIG. 2 is a cross-sectional view showing a layer structure of a cathode foil using an electrode material according to an embodiment of the present invention. [Diagram 2] FIG. 4 is a cross-sectional view (modification) showing a layer structure of a cathode foil using an electrode material in one embodiment of the present invention. [Diagram 3] 2 is a cross-sectional view showing the layer structure of a cathode foil using an electrode material in which layers are laminated only on one side of a substrate, unlike in FIG. 1, in one embodiment of the present invention. FIG. [Figure 4] 3 is a cross-sectional view showing the layer structure of a cathode foil using an electrode material in which layers are laminated only on one side of a substrate, unlike FIG. 2, in one embodiment of the present invention. FIG. [Diagram 5] 1 is an exploded view showing the structure of a wound-type solid electrolytic capacitor and a wound-type hybrid capacitor according to an embodiment of the present invention; [Figure 6]1 is a TEM (Transmission Electron Microscopy) photograph (cross-sectional image) of a cathode foil (Example 2 described below) using an electrode material according to one embodiment of the present invention. [Figure 7] 4 is a TEM photograph (cross-sectional image) of a cathode foil (Example 4 described later) using an electrode material according to another embodiment of the present invention. [Figure 8] 7 is a STEM (Scanning Transmission Electron Microscopy) photograph (cross-sectional image) of the same cathode foil (Example 2) as in FIG. 6. [Figure 9] 8 is a STEM photograph (cross-sectional image) of the same cathode foil (Example 4) as in FIG. 7. [Figure 10] TEM photographs (bright field image, cross-sectional image) of the same cathode foil (Example 2) as in FIG. 6. [Figure 11] 8 is a TEM photograph (bright field image, cross-sectional image) of the same cathode foil (Example 4) as in FIG. 7. [Figure 12] 7 is a graph showing the analysis results (showing a profile distribution of the chemical bond state) of the same cathode foil (Example 2) as in FIG. 6, by ToF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry). [Figure 13] 8 is a graph showing the analysis results by ToF-SIMS of the same cathode foil (Example 4) as in FIG. 7 (showing the profile distribution of the chemical bond state). [Figure 14] FIG. 8 is a graph of the Raman scattering spectrum (all wavenumber range) obtained by laser microscopic Raman spectroscopy of the same cathode foils (Examples 2 and 4) as those in FIGS. 6 and 7. [Figure 15] FIG. 8 is a graph of a Raman scattering spectrum (CC bond region) obtained by laser microscopic Raman spectroscopy of the same cathode foils (Examples 2 and 4) as those in FIGS. 6 and 7. [Figure 16] Narrow scan spectra due to C bond states obtained by XPS for the same cathode foils (Examples 2 and 4) as in Figures 6 and 7. [Figure 17]1 is a table showing the results of ESR measurements carried out on hybrid capacitor Examples 1 to 8 and hybrid capacitor Comparative Examples 1 to 6. [Figure 18] 1 is a table showing the results of ESR measurements carried out on solid electrolytic capacitors of Examples 1 to 8 and solid electrolytic capacitors of Comparative Examples 1 to 6. [Figure 19] 7 is a profile distribution of elements obtained by TEM-EDS (Transmission Electron Microscopy-Energy Dispersive X-ray Spectroscopy) of the same cathode foil (Example 2) as in FIG. 6. [Figure 20] Elemental profile distribution obtained by TEM-EDS for the same cathode foil (Example 4) as in FIG. 7. [Figure 21] 22 shows a profile distribution of elements (on the carbon conductive layer side from FIG. 22) obtained by STEM-EELS (Scanning Transmission Electron Microscopy-Electron Energy Loss Spectroscopy) of the same cathode foil (Example 2) as in FIG. 6 . [Figure 22] 21 shows a profile distribution of elements obtained by STEM-EELS for the same cathode foil (Example 2) as in FIG. 6 (on the substrate side from FIG. 21). [Figure 23] 24 shows a profile distribution of elements obtained by STEM-EELS for the same cathode foil (Example 4) as in FIG. 7 (on the carbon conductive layer side from FIG. 24). [Figure 24] 23 shows a profile distribution of elements obtained by STEM-EELS for the same cathode foil (Example 4) as in FIG. 7 (on the substrate side from FIG. 23). [Diagram 25] 1 is a table showing the results of a tape adhesion test carried out on the cathode foils of Examples 1, 2, 4, and 5 and the cathode foil of Comparative Example 1. [Figure 26]FIG. 8 is a table showing the results of contact angle measurements performed on the same cathode foils (Examples 2 and 4) as those in FIGS. 6 and 7 and the cathode foil of Comparative Example 1, and the breakdown of surface free energy (hydrogen bonding component and dispersion force component) calculated therefrom. [Figure 27] a) SEM (Scanning Electron Microscopy) photograph (surface image) of the same cathode foil (Example 2) as in Figure 6. b) SEM photograph (surface image) of the same cathode foil (Example 4) as in Figure 7. c) SEM photograph (surface image) of the cathode foil of Example 5. d) SEM photograph (surface image) of the cathode foil of Example 6. [Figure 28] 1 is a table showing the average diameter (Ferret's diameter) of Examples 1 to 6 and 8. [Figure 29] a) A graph showing the abundance of each element in the depth direction obtained by XPS (X-ray photoelectron spectroscopy) of the same cathode foil (Example 2) as in Figure 6. b) A graph showing the sum of each C bond state and the abundance of TiC bonds in the depth direction obtained by XPS of the same cathode foil (Example 2) as in Figure 6. [Diagram 30] 1 is a table showing the static friction coefficients and average kinetic friction coefficients of the cathode foils of Examples 2, 4, and 5 and the cathode foil of Comparative Example 1. [Diagram 31] FIG. 7 is a graph showing the G-band peak separated from the spectrum obtained by Raman spectroscopy of the same cathode foil (Example 2) as in FIG. 6. [Diagram 32] 1 is a table showing the magnification of the BET specific surface area measured by the Kr adsorption method relative to the BET specific surface area of ​​the smooth substrate for the cathode foil of each Example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] Hereinafter, as an embodiment of the present invention, a cathode foil for electrolytic capacitors using an electrode material and an electrolytic capacitor using the cathode foil will be described. However, as already mentioned, the aluminum foil used in the following description as a substrate and titanium (Ti) or aluminum (Al) for forming the first conductive layer can be replaced with other materials. For example, materials for forming the first conductive layer include tantalum (Ta), titanium (Ti), chromium (Cr), aluminum (Al), niobium (Nb), vanadium (V), tungsten (W), hafnium (Hf), copper (Cu), zirconium (Zr), zinc (Zn), and nitrides of these metals, oxides of these metals, oxynitrides of these metals, carbides of these metals, and carbonitrides of these metals (the first conductive layer may contain any material other than these. The same applies to other layers). Carbon is not limited to graphite-like carbon, and may be any carbon material. In addition, the use of the electrode material of the present invention is not limited to a cathode foil for a solid electrolytic capacitor or a hybrid capacitor, and the electrode material can be used for electrodes (any electrode such as a cathode, an anode, a positive electrode, or a negative electrode) of any storage element such as other secondary batteries, electric double layer capacitors, and lithium ion capacitors. The electrolytic capacitor of the present invention is not limited to a wound electrolytic capacitor described later, and may be any type such as a laminated type or a chip type. The uneven portion of the first conductive layer shown in FIG. 1 described later does not need to be formed on the entire surface of the surface side of the first conductive layer, and the uneven portion may be provided only partially on the surface side of the first conductive layer (obviously, the uneven portion may be formed on the entire surface of the surface side of the first conductive layer). The "smooth" substrate referred to in Figure 1 etc. described below does not necessarily have to have a smooth surface in its entirety; for example, a substrate having minute roughness or undulations on the surface due to unavoidable rolling marks or scars that occur slightly during the foil manufacturing process, such as rolling, is also included in the "smooth substrate" (it goes without saying that the substrate surface may be completely smooth).The "second conductive layer" described with reference to FIG. 1 and the like below may be a layer consisting essentially of carbon, or may be a layer containing other components than carbon, such as tantalum (Ta), titanium (Ti), chromium (Cr), aluminum (Al), niobium (Nb), vanadium (V), tungsten (W), hafnium (Hf), copper (Cu), zirconium (Zr), zinc (Zn), nitrides of these metals, oxides of these metals, oxynitrides of these metals, carbides of these metals, and carbonitrides of these metals. The carbon content in the second conductive layer may be any content. In addition, it is not essential that the electrode material, cathode foil for electrolytic capacitor, or electrolytic capacitor of the present invention have all of the layers, components, and structures described in the following embodiments, and the electrode material and cathode foil for electrolytic capacitor do not need to have a dense layer. In FIG. 1 described later, the first conductive layer and the like are formed on both sides of the smooth substrate, but various layers or elements such as unevenness may be provided on only one side of the smooth substrate or on both sides. It is also possible to configure an electrolytic capacitor having an electrode material or a cathode foil using an electrode material, such as by providing an oxide layer on the first side (front side) of the smooth substrate but not on the second side (rear side), and providing different layer structures on the first and second sides of the substrate, and the presence or absence, arrangement, etc. of elements such as unevenness on one side are different from those of the present invention. Other layers, elements, structures, features, etc. can be omitted as appropriate as long as the electrode material, cathode foil for electrolytic capacitor, or electrolytic capacitor of the present invention can function, and the electrode material, cathode foil for electrolytic capacitor, or electrolytic capacitor of the present invention may have layers, elements, structures, and features other than those described in the following embodiments as long as the electrode material or electrolytic capacitor of the present invention can function. In the electrolytic capacitor of the present invention, any of the electrode materials of the present invention can be used as the cathode foil. Each layer, element, structure, feature, etc. described may be arbitrarily selected and appropriately combined, and electrode materials, cathode foils for electrolytic capacitors, electrolytic capacitors, etc. obtained through such selection and combination are all included in the scope of the present invention.

[0032] The above-mentioned resistance to deterioration caused by the solid electrolyte, the chemical polymerization solution, the electrolytic solution, and moisture can be further improved by the following measures. If the adhesion at the interface between the smooth foil and the vapor deposition layer is insufficient, a vapor deposition layer may be applied after covering it with a dense inorganic conductive layer. By covering the smooth foil with a dense inorganic conductive layer, it is possible to completely eliminate the exposed aluminum part in one example, thereby improving chemical resistance and durability. By applying an oxide film containing phosphorus (P) to the smooth foil and then covering it with a dense inorganic conductive layer, it is possible to further improve chemical resistance and durability (even if a dense layer is not formed, it is possible to improve chemical resistance and durability by applying an oxide film containing phosphorus to the smooth base material through chemical conversion treatment, etc.).

[0033] Cathode foil using the electrode material of the present invention 1 is a cross-sectional view showing the layer structure of a cathode foil using an electrode material in one embodiment of the present invention. The cathode foil (electrode material) 1 has a base material (smooth aluminum foil) 2 that has not been roughened by etching or the like, an oxide layer 3 such as a natural oxide film or an artificially formed oxide film containing phosphorus formed on the smooth aluminum foil 2, a first conductive layer 4 formed on the oxide layer 3 and having projections and recesses made of Ti or Al, and a second conductive layer 5 formed on the first conductive layer 4. Furthermore, a mixed layer 7 is formed between the first conductive layer 4 and the second conductive layer 5.

[0034] A commercially available high-purity aluminum sheet can be used as the smooth aluminum foil 2. The thickness of the aluminum sheet is not particularly limited, but if it is used as a cathode foil for a wound-type electrolytic capacitor (such as a solid electrolytic capacitor or a hybrid capacitor), it is preferably 10 μm or more and 50 μm or less.

[0035] The oxide layer 3 is an oxide layer such as a natural oxide film or an oxide film intentionally formed by a chemical treatment such as anodizing or immersion treatment containing phosphorus, and is formed by exposing the smooth aluminum foil 2 to air, anodizing treatment using an ammonium dihydrogen phosphate solution, immersing in an aqueous phosphoric acid solution or an aqueous aluminum biphosphate solution followed by heat treatment, or the like.

[0036] In one example, the first conductive layer 4 is formed by arranging the smooth aluminum foil 2 on which the oxide layer 3 is formed, or, in the case of forming a dense layer 6 described later, the smooth aluminum foil 2 on which the dense layer 6 is formed on the oxide layer 3 by an arc ion plating method or the like in a vacuum chamber, and a metal material of Ti or Al as an evaporation source, and then evaporating the metal material and depositing the evaporated metal material on the oxide layer 3 (on the dense layer 6 in the case of forming the dense layer 6) (evaporation method). As the evaporation method, in addition to the above-mentioned vacuum evaporation method, a chemical vapor deposition (CVD) method, a sputtering method, etc. can be used, but among the vacuum evaporation methods, the electron beam evaporation method is preferable in terms of control of the geometric structure. The electron beam evaporation method is a method in which an accelerated electron beam is irradiated to an evaporation material to heat and vaporize it, and the material is deposited on a substrate. The fineness of the unevenness in the first conductive layer can be controlled, for example, by adjusting the particle size of the metal material to be deposited. The particle size of the metal material can be appropriately controlled by adjusting the conditions such as the type of gas introduced, the degree of vacuum, and the temperature of the substrate during deposition. In the embodiment in which the oxide layer 3 is formed and, in the case of forming a dense layer 6, the first conductive layer 4 made of a nitride, oxide, or carbide of a metal such as Ti or Al is formed on the smooth aluminum foil 2 on which the dense layer 6 is further formed, the first conductive layer 4 may be formed by carrying out the above method in an atmosphere of, for example, nitrogen gas, oxygen gas, or a hydrocarbon gas such as acetylene gas or methane gas. In the embodiment in which the first conductive layer 4 made of an oxynitride or carbonitride of a metal such as Ti or Al is formed, the first conductive layer 4 may be formed in an atmosphere of, for example, nitrogen gas and oxygen gas, or nitrogen gas and a hydrocarbon gas such as acetylene gas or methane gas.

[0037] The second conductive layer 5 of this embodiment is preferably formed by using a deposition method such as an ion plating method, rather than by dispersing carbon particles in a binder such as a resin binder and then applying the resulting mixture. In the layer of carbon particles formed by kneading with a binder, the carbon occupancy rate is substantially reduced by the amount of the binder mixed, and the contact between the material of the first conductive layer in the lower layer and the carbon particles is point contact, and it is difficult to form a mixed layer. Furthermore, with the above-mentioned application method, it is difficult to increase the electrical conductivity of the interface, the interface resistance increases, the adhesion deteriorates, and it is difficult to coat thinly and uniformly. The second conductive layer 5 is preferably formed as a smooth and dense GLC (Graphite-Like Carbon) coating. Carbon is measured by Raman spectroscopy to determine the G-band peak (sp 2 The larger the half-width obtained by separating the bonded portion, the higher the degree of amorphousness, and generally the density, hardness, Young's modulus, etc. increase. Therefore, the half-width of the carbon used in the second conductive layer 5 is set to be 3.8 times or more the half-width of crystalline graphite. By doing so, the second conductive layer 5 becomes a film with a high degree of amorphousness and excellent resistance to deterioration (chemical resistance and durability) against solid electrolytes, chemical polymerization chemicals, electrolytes, and moisture. Note that when the second conductive layer 5 is formed on the uneven portion of the first conductive layer 4, the shape of the second conductive layer 5 depends on the shape of the uneven portion of the first conductive layer 4, so the second conductive layer 5 does not necessarily have to have unevenness (its thickness is substantially constant), and may be a smooth and dense coating. As shown in Figures 1 to 4, since the surface of the surface side of electrode material 1 has irregularities, it is considered that the static friction coefficient and kinetic friction coefficient of the surface of the surface side of electrode material 1 against the separator paper are higher than the static friction coefficient and kinetic friction coefficient of the surface of the surface side of an electrode material that has a conductive layer that is the outermost layer on the surface side and is made of carbon on a smooth base material and has no irregularities on the surface side.

[0038] The second conductive layer 5 is obtained by the same method as the dense layer 6, but among them, an ion plating method such as an arc ion plating method, which has a high ionization rate and adhesion energy of the film-forming material, is one of the preferred methods because it is easy to form a mutual diffusion state with the first conductive layer and has a high effect of reducing the interface resistance. Specifically, a laminate in which an oxide layer 3 and a first conductive layer 4 are formed on a smooth aluminum foil 2 (when forming a dense layer 6, a dense layer 6 is further formed between the oxide layer 3 and the first conductive layer 4) and a carbon material as an evaporation source (for example, a graphite material when forming the second conductive layer 5 as a GLC coating) are placed in a vacuum chamber, and the carbon material is evaporated and ionized by generating a vacuum arc discharge between the evaporation source target as a cathode and an anode, and the carbon cations generated by this are guided to the laminate. The arc ion plating method is suitable for forming a high melting point compound film such as a carbide or nitride because it can generate high Joule heat locally on the target by the arc current and can increase the ionization rate of the evaporated film material due to the high plasma density. At this time, a negative bias voltage may be applied to the laminate in order to accelerate the carbon cations toward the laminate. When the second conductive layer 5 is to have an uneven geometric shape, a carbon material (for example, a graphite material when the second conductive layer 5 is formed as a GLC coating) may be introduced using the same electron beam evaporation method as that used for the uneven portion of the first conductive layer 4. The second conductive layer 5 may contain any component other than carbon, but when forming the second conductive layer 5 containing a component other than carbon, any other material may be prepared in addition to the carbon material as an evaporation source, and not only the carbon material but also the other material may be evaporated and ionized in the same manner to be introduced into the laminate.

[0039] In one example, the mixed layer 7 can be formed by not completely separating the step of forming the first conductive layer 4 by a deposition method such as vacuum deposition as described above from the step of forming the second conductive layer 5 by arc ion plating as described above, but by performing both steps so that there is a time when the steps of forming the first conductive layer 4 and forming the second conductive layer 5 are performed simultaneously. By introducing such a mixed layer 7, the adhesion and chemical stability between the material constituting the first conductive layer 4 (metal, or any material including metal nitride, oxide, oxynitride, carbide, or carbonitride as described above) and the material constituting the second conductive layer 5 (carbon such as GLC, and any other material contained in the second conductive layer 5 when the second conductive layer 5 contains materials other than carbon) are improved, and deterioration due to chemical reaction of the metal is prevented.

[0040] It is preferable that the mixed layer 7 is configured so that the boundary region with the first conductive layer 4 contains substantially only the material constituting the first conductive layer 4, and the boundary region with the second conductive layer 5 contains substantially only the material constituting the second conductive layer 5, and that the content of the material constituting the second conductive layer 5 increases continuously from the first conductive layer 4 toward the second conductive layer 5. An example of such a mixed layer 7 is as follows: (i) At the start of the formation of the mixed layer 7, only the deposition method, which is the step of forming the first conductive layer 4, is performed, and the electron beam is not irradiated onto the carbon material such as a graphite material (and, in the case where the second conductive layer 5 contains materials other than carbon, any other material of the second conductive layer 5); (ii) gradually reducing the amount of electron beam irradiation to the material constituting the first conductive layer 4 over time to reduce the amount of evaporation of the metal material in the vapor deposition method which is the process of forming the first conductive layer 4, and at the same time increasing the amount of electron beam irradiation to the carbon material such as a graphite material (and, in the case where the second conductive layer 5 also contains materials other than carbon, any other material of the second conductive layer 5), thereby forming a mixed coating in which the material constituting the first conductive layer 4 and the material constituting the second conductive layer 5 are mixed and the content of the material constituting the second conductive layer 5 increases toward the upper layer, (iii) At the end of the film formation, the deposition method, which is the step of forming the first conductive layer 4, is terminated, and only the arc ion plating method, which is the step of forming the second conductive layer 5, is carried out, thereby forming a film consisting essentially of only the material that constitutes the second conductive layer. In addition, when the mixed layer 7 is formed by a vapor deposition method (first conductive layer 4) and a sputtering method (second conductive layer 5), the mixed layer 7 of such a preferred embodiment can be formed by any method, such as decreasing the amount of evaporation of the material of the first conductive layer 4 over time and increasing the voltage applied to a carbon target such as a graphite target (and, if the second conductive layer 5 contains materials other than carbon, any other target of the material of the second conductive layer) (increasing the sputtering rate of the graphite target and, if used, the other target of the material of the second conductive layer). In addition, (i) to (iii) are processes mainly suitable for batch-type sheet processing, but alternatively, the mixed layer can also be formed by performing continuous film formation processing in the order of the first and second while conveying the foil in a chamber in which a material target constituting the first conductive layer and then a material target constituting the second conductive layer are arranged in that order by a roll-to-roll method. The first and second evaporation source targets are arranged adjacent to each other so that the vapors or ions of the deposition materials emitted from the first and second evaporation source targets in a cone shape toward the substrate overlap (contact) each other before reaching the substrate, thereby forming a mixed layer. The mixed layer is adjusted to an optimal state in terms of the mixing, diffusion, and bonding states by appropriately controlling the distance between the evaporation source targets and the distance between each evaporation source target and the substrate. In this case, the electron beam irradiation amount does not need to be adjusted as described above, and can be kept constant, making this a process more suitable for mass production. The mixed layer may also be obtained by heating the substrate temperature to, for example, several hundred degrees Celsius, regardless of the distance between the evaporation source targets and the distance between each evaporation source target and the substrate.

[0041] Fig. 2 is a cross-sectional view (modification) showing the layer structure of a cathode foil using an electrode material according to one embodiment of the present invention. Unlike the layer structure in Fig. 1, a dense layer 6 is formed between an oxide layer 3 and a first conductive layer 4.

[0042] The dense layer 6 is formed by arranging the smooth aluminum foil 2 on which the oxide layer 3 is formed and a metal material of Ti or Al as an evaporation source in a vacuum chamber, evaporating and ionizing Ti or Al with an electron beam and a plasma generating electrode, etc., and guiding the metal cations generated by the arc discharge to the smooth aluminum foil 2. At this time, a negative bias voltage may be applied to the smooth aluminum foil 2 in order to accelerate the metal cations toward the smooth aluminum foil 2. Therefore, the Ti or Al ions penetrate the oxide layer 3 formed on the surface of the smooth aluminum foil 2 and firmly adhere to the smooth aluminum foil 2. However, it is not essential that the material of the first conductive layer 4 and the smooth aluminum foil 2 are adhered to each other through the oxide layer 3, and the oxide layer 3 such as a natural oxide film or an oxide film by anodizing treatment containing phosphorus may be present between the first conductive layer 4 and the smooth aluminum foil 2 without having holes or the like. In an embodiment in which a dense layer 6 made of a nitride, oxide, or carbide of a metal such as Ti or Al is formed on the smooth aluminum foil 2 on which the oxide layer 3 is formed, the dense layer 6 may be formed by carrying out the above method in an atmosphere of, for example, nitrogen gas, oxygen gas, or a hydrocarbon gas such as acetylene gas or methane gas. In an embodiment in which a dense layer 6 made of an oxynitride or carbonitride of a metal such as Ti or Al is formed, the dense layer 6 may be formed in an atmosphere of, for example, nitrogen gas and oxygen gas, or nitrogen gas and a hydrocarbon gas such as acetylene gas or methane gas.

[0043] In addition to ion plating methods such as arc ion plating, vacuum deposition, chemical vapor deposition, sputtering, atomic layer deposition, sol-gel, plating, coating, printing, etc. can be used as a method for forming the dense layer 6. In one example, the ion plating method can be used because the dense layer 6 and the smooth aluminum foil 2 are firmly attached to each other through the oxide layer 3, thereby suppressing the ESR of the capacitor to a low level, and because a smooth metal coating can be easily formed.

[0044] As already mentioned, it is not essential to laminate the layers on both sides of the substrate 2 as shown in FIG. 1 or 2. The layers may be laminated on only one side of the substrate 2 as shown in FIG. 3 or 4. Alternatively, different layer structures may be formed on the front and back sides of the substrate 2, for example, by laminating the layers shown in FIG. 3 on one side of the substrate 2 and laminating the layers shown in FIG. 4 on the other side of the substrate 2.

[0045] The thickness of the oxide layer 3, the dense layer 6, the first conductive layer 4, the mixed layer 7, and the second conductive layer 5 is sufficient if it is about 0.005 μm or more and 1 μm or less, and good characteristics as a cathode foil can be obtained if the total thickness of each layer excluding the base material 2 is at least 0.05 μm on one side of the base material 2. However, each layer may be formed thicker or thinner. The thickness of each layer in FIG. 1 to FIG. 4 is merely an example, and the thickness of each layer can be determined arbitrarily.

[0046] It is important to determine the actual surface area of ​​the electrode material 1 by the BET specific surface area method for adsorbing nitrogen gas or krypton gas as an index of the retention of solid electrolyte or electrolyte solution, but in the present invention, in order to obtain the electrochemical effective surface area taking into account the ease of electrical flow such as the resistance of the interface, which is important when the material is made into an actual capacitor, evaluation was performed by the cyclic voltammetry method. The voltage was swept linearly under the conditions of 1M tetraethylammonium hexafluorophosphate with propylene carbonate as the solvent as the electrolyte, Pt electrode as the reference electrode, stainless steel as the counter electrode, electrolyte temperature of 30°C, sweep range of ±0.3V vs Pt electrode, and sweep speed of 500mV / sec, and the maximum current value of the cyclic voltammogram measured when the electrode material of the present invention was used as the working electrode was compared with the maximum current value measured when the smooth substrate was used as the working electrode, to obtain an index regarding the electrochemical effective surface area. The maximum current value when the electrode material of the present invention was used as the working electrode was set to be 6.5 times or more of the maximum current value when the smooth substrate was used as the working electrode. By using an electrode material that is 6.5 times thicker than when a smooth substrate is used as the working electrode, it is possible to reduce ESR by improving the retention of the solid electrolyte and electrolyte.

[0047] As an evaluation method for the bonds between atoms of metal elements and carbon atoms that make up the first conductive layer, XPS can be used to analyze the abundance of each element in the depth direction and the state of bonds. By repeating etching and measurement every few nm, it is possible to analyze the ratio of the abundance of bonds between atoms of metal elements that make up the first conductive layer and carbon atoms to the total abundance of all bonds involving the detected carbon atoms. Therefore, if this ratio is 5% or more, it becomes a low-resistance conductor, and the ESR reduction effect can be achieved.

[0048] In addition, when the electrode material according to an embodiment of the present invention using a valve metal as the substrate 2 is used as a cathode foil of an electrolytic capacitor, the potential corresponding to the current flowing due to electrochemical polarization within the current density range of the leakage current of the electrolytic capacitor may be more noble than the natural immersion potential of a control cathode foil of the same type as the valve metal used in the substrate 2 and having a purity of 99.99% or more, and the natural immersion potential when immersed in an electrolytic solution may be more noble than the natural immersion potential of a control cathode foil of the same type as the valve metal used in the substrate 2 and having a purity of 99.99% or more when immersed in the same electrolytic solution (Patent Documents 26 and 27). In this way, when the dielectric oxide film formed on the anode foil is repaired by the leakage current, it is possible to suppress the generation of hydrogen gas on the cathode side. To further explain this point, the above-mentioned control cathode foil has a natural oxide film formed thereon and has a natural immersion potential at which a cathode reaction that reduces hydrogen ions occurs predominantly. The cathode foil of the present invention has a natural immersion potential that is more noble than the above-mentioned control cathode foil. Therefore, even when the cathode foil of the present invention is incorporated into an electrolytic capacitor and leakage current occurs, the potential of the cathode foil of the present invention can be maintained on the noble side of the natural immersion potential of the above-mentioned control cathode foil. Therefore, when leakage current occurs in the electrolytic capacitor, the potential of the cathode foil of the present invention is within a potential range in which the cathodic reaction that reduces dissolved oxygen occurs predominantly, and the cathodic reaction that reduces hydrogen ions is suppressed. As a result, the increase in internal pressure of the electrolytic capacitor due to the generation of hydrogen gas is suppressed, and the risk of the case housing the capacitor element swelling can be reduced.

[0049] As described above, the BET specific surface area method in which nitrogen gas or krypton gas is adsorbed can be used to determine the actual surface area required for the inorganic conductive layer having uneven portions on the surface side including the first conductive layer and the second conductive layer to hold the solid electrolyte and the electrolyte solution. Among them, when krypton gas, which has a lower saturated vapor pressure than nitrogen gas, is used as the adsorption gas, high-precision measurement is possible even in areas with a small specific surface area. It is preferable that the surface expansion ratio (BET specific surface area of ​​electrode material / BET specific surface area of ​​smooth substrate) calculated from the BET specific surface area using krypton gas as the adsorption gas is 1.5 or more. By setting this surface expansion ratio to 1.5 times or more, the retention of the solid electrolyte and the electrolyte solution can be further improved, and a further ESR reduction effect can be obtained. However, although it is possible to further increase the surface area by making the first conductive layer thicker, if it is made too thick, the volumetric efficiency of the capacitor decreases and the manufacturing cost increases. Therefore, it is more preferable that the surface expansion ratio calculated from the BET specific surface area using krypton gas as the adsorption gas is 1.5 times or more and 200 times or less.

[0050] 27a) to 27d) are scanning electron microscope (SEM) surface photographs of the cathode foils of Examples 2, 4, 5, and 6. Here, the SEM photographs show what appear to be particles, which are the convex portions of the uneven portion on the surface side of the electrode material, that is, the surface side of the inorganic conductive layer. As described above, the electrode material 1 has an oxide layer 3, a first conductive layer 4, a mixed layer 7, and a second conductive layer 5 formed in this order on a smooth substrate 2, and has an uneven portion on the surface side of the first conductive layer 4. In Examples 2, 4, 5, and 6, the first conductive layer is a particle deposition layer formed by vapor deposition, and the mixed layer and the second conductive layer are formed thereon, but both the mixed layer and the second conductive layer are thin. Then, when the surface of the cathode foil of each Example is observed by SEM, it appears as if a sample in which only the first conductive layer, which is a particle deposition layer, is formed is observed, as shown in FIGS. 27a) to 27d). That is, each particle confirmed in the SEM surface photograph corresponds to each convex part of the inorganic conductive layer. Therefore, in Examples 2, 4, 5, and 6, the particle diameter of the particle confirmed in the SEM surface photograph was taken as the diameter of the convex part of the uneven part on the surface side of the inorganic conductive layer. Specifically, the surface of the cathode foil of each Example was observed at a magnification of 100,000 times using a JEOL JSM-7401F scanning electron microscope, and the Feret diameter of the particle present in the observation field at that time was measured, and the Feret diameter was taken as the diameter of the convex part. Note that the Feret diameter here refers to the distance between the left tangent line and the right tangent line of the particle parallel to the vertical direction of the field of view among the tangent lines to the particle, as shown in FIG. 27a). If the diameter of the convex part is too large, the surface area of ​​the uneven part on the surface side of the surface of the electrode material becomes small, and a geometric structure necessary for holding the solid electrolyte and the electrolyte cannot be obtained. Therefore, in addition to setting the surface expansion ratio calculated from the BET specific surface area using krypton gas as the adsorption gas to 1.5 times or more, it is more preferable to set the average diameter of the convex parts of the uneven portion on the surface side of the inorganic conductive layer to 210 nm or less, and it is even more preferable to set the surface expansion ratio calculated from the BET specific surface area using krypton gas as the adsorption gas to 1.5 times or more and 200 times or less, and to set the average diameter of the convex parts of the uneven portion on the surface side of the inorganic conductive layer to 210 nm or less.The average diameter here refers to the average Feret's diameter measured for 50 particles (protrusions) present in the observation field. However, if the number of particles in one field is less than 50, measurements are made in another field until the number of particles reaches 50.

[0051] Electrolytic capacitor of the present invention Hereinafter, a solid electrolytic capacitor and a hybrid capacitor will be described as examples of electrolytic capacitors that can be produced using the cathode foil of the present invention. Here, a case where a cathode foil 1 having a layer structure shown in Fig. 1 or 2 in which each layer is laminated on both sides of a substrate 2 is used will be described, but the electrolytic capacitor of the present invention can also be produced using a cathode foil 1 having a layer structure in which each layer is laminated on only one side of a substrate 2.

[0052] (Solid electrolytic capacitor) FIG. 5 is an exploded view of a wound type solid electrolytic capacitor 8 produced using a cathode foil 1 having the layer structure shown in either FIG. 1 or FIG. 2. The solid electrolytic capacitor 8 is (i) Anode foil 9 obtained by forming an oxide film on anodized aluminum foil by anodizing treatment and cathode foil 10 having any of the layer structures shown in FIG. 1 or 2 are stacked together with separator paper 11 interposed therebetween, and anode terminal 13 is connected to anode foil 9 and cathode terminal 14 is connected to cathode foil 10. The resulting structure is then wound to produce capacitor element 12. (ii) The capacitor element 12 is immersed in a mixed solution of 3,4-ethylenedioxythiophene, containing n-butyl alcohol as a diluent, and iron (II) p-toluenesulfonate as an oxidant, and then heated to form a solid electrolyte layer of polyethylenedioxythiophene (PEDOT) by thermal polymerization. Alternatively, the solid electrolyte layer may be formed by immersing and impregnating the capacitor element 12 in a PEDOT / PSS aqueous dispersion solution in which polyethylenedioxythiophene is mixed with polystyrenesulfonic acid (PSS) to disperse the polyethylenedioxythiophene in an aqueous solution, and then drying the PEDOT / PSS aqueous dispersion solution. (iii) Capacitor element 12 with the solid electrolyte layer formed thereon is housed in aluminum case 15 and sealed with sealing rubber 16. The solid electrolyte layer may be formed from conductive polymers such as polypyrrole, polyaniline, polyacene, polyparaphenylenevinylene, and polyisothianaphthene, or from manganese dioxide (MnO2) and TCNQ (tetracyanoquinodimethane) complex salts.

[0053] (Hybrid Capacitor) The hybrid capacitor is produced by carrying out steps (i) and (ii) in the same manner as in the production of the solid electrolytic capacitor 8, and then: (ii-2) The capacitor element having the solid electrolyte layer formed thereon is impregnated with an electrolyte solution containing at least one of γ-butyrolactone, ethylene glycol, and water as a solvent. (iii) The solid electrolyte layer is formed, and the capacitor element impregnated with the electrolyte is housed in an aluminum case and sealed with sealing rubber. The solid electrolyte layer may be formed from conductive polymers such as polypyrrole, polyaniline, polyacene, polyparaphenylenevinylene, and polyisothianaphthene, or from manganese dioxide (MnO2) and TCNQ (tetracyanoquinodimethane) complex salts. EXAMPLES

[0054] The structures, analysis results, performance test results, etc. of various cathode foils and electrolytic capacitors produced as examples of the present invention will be described below.

[0055] FIG. 6 is a TEM (transmission electron microscope) photograph (cross-sectional image) of a cathode foil (Example 2 described below) using an electrode material according to one embodiment of the present invention. The cathode foil in FIG. 6 has the layer structure shown in FIG. 4 (the layer structure on one side shown in FIG. 2) (it is believed that a natural oxide film is formed between the smooth substrate and the dense layer), and is produced by forming a dense layer 6 of Ti by arc ion plating on an aluminum smooth substrate 2 (on which a natural oxide film 3 is formed), forming a first conductive layer 4 of Ti by vacuum deposition, and forming a carbon layer (second conductive layer 5) of GLC by arc ion plating. Such a cathode foil is, By using a smooth substrate as the substrate 2, the Al surface can be coated with Ti without any gaps. The granular deposition structure enables the polymer and electrolyte to adhere and be retained. · Ti pretreatment using the arc ion plating method can eliminate the effects of residual oil and oxides on the substrate surface. 7 shows a TEM photograph (cross-sectional image) of a cathode foil (Example 4 described later) different from the cathode foil shown in FIG. 6. The cathode foils shown in FIG. 6 and FIG. 7 are common in that they are both produced by forming a dense layer 6 of Ti on a smooth aluminum substrate 2 (having a natural oxide film 3 formed thereon) by an arc ion plating method, forming a first conductive layer 4 of Ti by a vacuum deposition method, and forming a carbon layer (second conductive layer 5) of GLC by an arc ion plating method, but the particle diameter of the metal material (Ti in the samples in FIG. 6 and FIG. 7) contained in the first conductive layer 4 is different from each other, and therefore the fineness of the unevenness in the first conductive layer 4 is different from each other.

[0056] Fig. 8 is a STEM (scanning transmission electron microscope) photograph (cross-sectional image) of the same cathode foil (Example 2) as in Fig. 6, and Fig. 9 is a STEM photograph (cross-sectional image) of the same cathode foil (Example 4) as in Fig. 7. As described above, the particle size of the metal material in the first conductive layer 4 can be appropriately controlled by adjusting conditions such as the type of gas introduced, the degree of vacuum, and the temperature of the base material during deposition, so that the first conductive layer 4 can be formed with various particle sizes, i.e., with various finenesses of unevenness.

[0057] Figure 10 is a TEM photograph (bright field image, cross-sectional image) of the same cathode foil (Example 2) as in Figure 6, and Figure 11 is a TEM photograph (bright field image, cross-sectional image) of the same cathode foil (Example 4) as in Figure 10. In both samples of Example 2 and Example 4, a natural oxide film (about several nm) on the substrate can be identified.

[0058] FIG. 12 is a graph showing the analysis results (showing the profile distribution of the chemical bond state) of the same cathode foil (Example 2) as in FIG. 6 by ToF-SIMS (time-of-flight secondary ion mass spectrometry), and FIG. 13 is a graph showing the analysis results (showing the profile distribution of the chemical bond state) of the same cathode foil (Example 4) as in FIG. 7 by ToF-SIMS. In the graphs of FIG. 12 and FIG. 13, the vertical axis represents the secondary ion intensity (Intensity), and the unit is [counts] representing the number of secondary ions detected at each measurement depth point. In the graphs of FIG. 12 and FIG. 13, carbon C6 derived from carbon deposition is a fragment (lump) ion consisting of six C atoms and is a monovalent negative ion, metal titanium Ti2 ion is a monovalent negative ion consisting of two Ti atoms, metal aluminum (base metal) Al5 ion is a monovalent negative ion consisting of five Al atoms, and other ions such as TiC2 / TiO2 / TiN / TiNO / Al2O3 are negative ions in their respective molecular bond states. For example, in Example 4 shown in Figure 13, it can be seen that there is only a small amount of metallic Ti at the substrate interface, with most of it existing as carbides / oxides / nitrides / oxynitrides. It can also be seen that in both samples of Example 2 and Example 4, a mixed layer of oxides and Ti compounds, and a mixed layer of Ti compounds and C are formed on the aluminum substrate, and that the mixed layers are formed as gradient coatings in which the proportion of C increases toward the outermost layer (carbon layer).

[0059] Fig. 14 is a graph (all wavenumber region) of the Raman scattering spectrum obtained by laser microscopic Raman spectroscopy of a cathode foil as a sample prepared under the same conditions as the samples shown in Figs. 6 and 13, and Fig. 15 is a graph (CC bond region) of the Raman scattering spectrum obtained by laser microscopic Raman spectroscopy of a cathode foil as a sample prepared under the same conditions as the samples shown in Figs. 6 and 13. In the graph of Fig. 14, the horizontal axis of the Raman shift is 1500 cm -1 The graph with the larger Raman intensity [counts] on the vertical axis corresponds to the sample of Example 2, and the Raman shift on the horizontal axis corresponds to 1500 cm -1 The graph with the smaller Raman intensity [counts] on the vertical axis in the vicinity of 1100 cm corresponds to the sample of Example 4. In the graph of FIG. -1 The graph with the smaller Raman intensity [counts] on the vertical axis corresponds to the sample of Example 2, and the Raman shift on the horizontal axis corresponds to 1100 cm -1 The graph with the larger Raman intensity [counts] on the vertical axis in the vicinity corresponds to the sample of Example 4. In particular, from the graph shown in FIG. 15, it can be seen that in both samples of Example 2 and Example 4, the sp 3 (D band) 2 The Raman intensity at (G band) is higher than that at (G band), indicating that the carbon layer (second conductive layer) in both samples is formed by containing GLC.

[0060] Figure 16 shows a spectrum obtained by narrow-range scanning in the 280-290 eV range at a point 36 nm etched from the surface of a cathode foil prepared under the same conditions as the samples shown in Figures 6 and 7. The peaks due to the C bond state observed in the vicinity of 280-290 eV were separated, and a sp 2 The peak due to sp 3 Therefore, it can be seen that the carbon layers in both samples of Example 2 and Example 4 have an amorphous structure (non-crystalline structure) with bonds of both graphite and diamond. In addition, a comparison of the peak areas reveals that the peaks due to sp3 More than sp 2 It can be seen that the peak area is larger in the sample A. Therefore, it can be seen from not only the laser micro-Raman spectroscopy analysis but also from the XPS that the carbon layers in both samples are formed from graphite-like carbon with a graphite bond ratio exceeding 50%.

[0061] Figure 29a) is a graph showing the bonding state in the depth direction obtained by XPS of a sample prepared under the same conditions as the sample shown in Figure 6. By repeating etching and measurement in units of several nm from the surface layer, the abundance in the depth direction as shown in Figure 29a) is shown. Figure 29b) is a graph showing the total of all C bonding states and TiC bonds when the peak due to the C bonding state is separated as in Figure 16 until C is no longer detected for the sample shown in Figure 6, with the horizontal axis being the SiO2 equivalent depth and the vertical axis being the peak area for each C bonding state (Note that in the sample analyzed in Figure 29, the metal element constituting the first conductive layer is titanium, so the "TiC bond" corresponds to the "bond between the atom of the metal element constituting the first conductive layer and the carbon atom."). The integral value was calculated for each curve, and the abundance of the TiC bonding state (near 282 eV) divided by the abundance of all C bonding states was determined as the abundance ratio of TiC bonds. In the case of other metal carbides, the calculation can be made from peaks such as the Al4C3 bonding state (near 282.4 eV), TaC bonding state (near 281.9 eV), NbC bonding state (near 281.9 eV), VC bonding state (near 282.5 eV), and WC bonding state (near 283.0 eV).

[0062] Performance test of the hybrid capacitor of the present invention The cathode foils of Examples 1 to 8 were prepared as the cathode foils of the present invention, and the cathode foils of Comparative Examples 1 to 6 were prepared as the cathode foils of the comparative examples. The hybrid capacitors of Examples 1 to 8 were fabricated using the cathode foils of Examples 1 to 8, respectively, and the hybrid capacitors of Comparative Examples 1 to 6 were fabricated using the cathode foils of Comparative Examples 1 to 6, respectively, and a performance test (ESR measurement) was performed for each of the fabricated hybrid capacitors. The fabrication conditions and ESR measurement conditions for each hybrid capacitor are as follows: Example 1: Ar gas is introduced into a chamber vessel evacuated to 0.003 Pa, and a first target made of a Ti material and a second target made of a graphite material are sequentially placed adjacent to each other in a process such that the vapor and ions of the deposition materials emitted in a cone shape from the first and second targets toward the substrate overlap (come into contact) before they reach the substrate. A smooth aluminum foil is transported in this order into the process, and a 200 nm uneven Ti layer is applied by electron beam evaporation, and then a carbon film is formed by arc ion plating. By this continuous film formation by the roll-to-roll method, a mixed layer was obtained at the interface between the oxide layer on the smooth substrate and the first conductive layer, and at the interface between the first conductive layer and the second conductive layer. (Note that the mixed layer formed at the interface between the oxide layer and the first conductive layer is a mixture of the material constituting the oxide layer and the material constituting the first conductive layer, and is different from a mixture of the material constituting the first conductive layer and the material constituting the second conductive layer.) The foil was used as a cathode and combined with an anode foil (etched aluminum chemical foil anodized at 53 V) to prepare a hybrid capacitor, and the initial ESR (100 kHz) was measured, and the ESR (100 kHz) was measured after leaving it at 125°C for 2000 hours (1 hour is 60 minutes). The hybrid capacitor was prepared as follows. That is, first, the anode foil and the cathode foil prepared as described above were stacked with a separator paper between them, and the anode terminal was connected to the anode foil and the cathode terminal was connected to the cathode foil, and then the resultant was wound to prepare a capacitor element. Next, the capacitor element was immersed in a water-solvent polymer dispersion solution in a container evacuated to about 7000 Pa, and then dried at 150°C for 30 minutes in an air environment to form a solid electrolyte layer. Furthermore, the capacitor element was impregnated with an electrolyte solution containing ethylene glycol as a solvent in a container evacuated to about 5000 Pa. Finally, the capacitor element was housed in an aluminum case and sealed with a sealing rubber. Example 2: The same amount of Ar gas as in Example 1 is introduced into a chamber vessel evacuated to 0.003 Pa, a smooth aluminum foil is conveyed, and a Ti film of 10 nm is formed by arc ion plating. After that, the aluminum foil on which a Ti layer is formed by arc ion plating is conveyed into the same film formation process as in Example 1, a Ti layer with an unevenness of 200 nm is applied by vapor deposition, and a carbon film is formed by arc ion plating. The rest is the same as in Example 1. Example 3: The same treatment as in Example 2 was carried out, except that a smooth substrate was used that had been anodized in an ammonium dihydrogen phosphate solution at an applied voltage of 5V. Example 4: This example is the same as Example 2, except that the gases introduced are Ar and N2. Example 5: Same as Example 2, except that the roughened Ti layer applied by vapor deposition is 70 nm. Example 6: This is the same as Example 2, except that an Al film is formed instead of Ti by arc ion plating, and then an uneven Al layer is applied by vapor deposition instead of the uneven Ti layer. Example 7: The conditions were the same as in Example 2, except that the amount of Ar gas introduced was 1 / 40 of that in Example 2. Example 8: The conditions were the same as in Example 6, except that the amount of Ar gas introduced was one tenth of that in Example 6. Comparative Example 1: A smooth substrate was used, the same amount of Ar gas was introduced as in Examples 1 to 3, a Ti film was formed by arc ion plating, and then a carbon film was formed by arc ion plating, which was used as a cathode. The other conditions were the same as in Example 1. Comparative Example 2: An etched foil anodized at 2V was used as the substrate, the same amount of Ar gas as in Examples 1 to 3 was introduced, a Ti film was formed by arc ion plating, and a carbon film was formed by arc ion plating, which was used as the cathode. The other conditions were the same as in Example 1. Comparative Example 3: A (dense) Ti layer was formed by vacuum deposition on a smooth substrate without introducing any gas, and then N2 gas was introduced until the pressure inside the container became equivalent to that of Examples 1 to 3, and a (rough) Ti layer was formed by vacuum deposition, which was then used as a cathode. The other conditions were the same as those of Example 1. The coating structure of the cathode foil of Comparative Example 3 is the same as the coating structure disclosed in the specification of JP 2014-022707 A. Comparative Example 4: This is the same as Example 2, except that the uneven Ti layer provided by vapor deposition was 30 nm thick. Comparative Example 5: The same as Example 1, except that an Al layer was provided by deposition instead of the uneven Ti layer. Comparative Example 6: The same as Example 2, except that only N2 gas was introduced. In the cathode foils of Examples 1 to 8 and Comparative Examples 1, 2, and 4 to 6 in which a carbon conductive layer is formed, a mixed layer is formed under the carbon conductive layer. In the mixed layer, carbon and a material constituting the layer under the mixed layer are mixed and exist. In addition, the carbon layers in Examples 1 to 8 and Comparative Examples 1, 2, and 4 to 6 contain GLC.

[0063] The current value flowing through the cathode foils of the examples and comparative examples was measured by cyclic voltammetry. The measurement was performed under a nitrogen atmosphere using a glove box. 1M tetraethylammonium hexafluorophosphate with propylene carbonate as the solvent was prepared as the measurement solution. The measurement was performed using a three-electrode system, with stainless steel as the counter electrode, a Pt electrode as the reference electrode, and the cathode foil of each example or comparative example as the working electrode. The measurement conditions for cyclic voltammetry were a measurement solution temperature of 30°C, a sweep range of ±0.3V, and a sweep speed of 500mV / sec. The current and voltage were recorded for 1 to 5 cycles, the maximum value of the current for each cycle was calculated, and the average value was taken as the maximum current value of the cathode foil of the example or comparative example. Similarly, the maximum current value was measured for the smooth substrate alone, and the maximum current value was set to 1 to display the maximum current value of the cathode foil of each example and comparative example.

[0064] For the cathode foils of the examples and comparative examples, etching and measurement were repeated in increments of 2.5 nm in terms of SiO2 by XPS to confirm the bonding state in the depth direction. The XPS device used was a JPS-9010TR manufactured by JEOL Ltd., and the measurements were performed under the following conditions. X-ray source: AlKα, tube voltage: 10kV, tube current: 10mA, microanalysis: none, dwell: 100msec, flood gun: 3.0V 4.0mA Step: Wide range 1.0eV / Narrow range 0.05eV Pass: Wide range 50eV / Narrow range 20eV Scans: Wide range 1 / Narrow range 2 Peaks due to C bonding states observed near 270 eV to 290 eV measured in a measurement range of 0.05 eV were separated, and the peak area was calculated for each C bonding state. The integral value of the curve drawn when the horizontal axis is the SiO2 converted depth and the vertical axis is the peak area of ​​each C bonding state was calculated, and this was taken as the abundance of each C bonding state. The value obtained by dividing the abundance of the TiC bonding state (near 282 eV) or the Al4C3 bonding state (near 282.4 eV) by the abundance of all C bonding states was taken as the abundance ratio of the bonds between atoms of metal elements and carbon atoms in the cathode foils of each Example and Comparative Example.

[0065] For the cathode foils of the examples and comparative examples, the sp 2 The half-width of the G-band peak was measured. Figure 31 shows an example of a spectrum resulting from C-C bonds obtained by Raman spectroscopy of the sample shown in Figure 6. The spectrum was separated and the half-width of the G-band peak was measured. A Renishaw inVia Qontor was used for the measurement, and a laser with a wavelength of 532 nm was irradiated, and the half-width of the G-band peak was measured. -1 Similarly, the half-width of crystalline graphite was measured, and this was taken as 1, and used as the magnification of the half-width of each Example and Comparative Example.

[0066] FIG. 17 is a table showing the results of ESR measurement performed on the hybrid capacitors of Examples 1 to 8 and the hybrid capacitors of Comparative Examples 1 to 6. In FIG. 17, "after 2000 hr aging" indicates that the ESR was measured after the hybrid capacitor was aged for 2000 hours in an atmospheric environment at 125°C. As can be seen from the ESR measurement results in FIG. 17, first, in the initial state, the ESR of the hybrid capacitors of Examples 1 to 3, 6, and 7 is lower than the ESR of the hybrid capacitors of Comparative Examples 1 to 6, and the ESR of the hybrid capacitors of Examples 4, 5, and 8 is lower than the ESR of the hybrid capacitors of Comparative Examples 1 and 3 (note that the ESR of the hybrid capacitors of Comparative Examples 2, 4, 5, and 6 is almost the same). After 2000 hr aging, the ESR of the hybrid capacitors of Examples 1 to 8 is lower than the ESR of the hybrid capacitors of Comparative Examples 1 to 6.

[0067] 17 also shows the results of measurements by cyclic voltammetry, XPS, and Raman spectroscopy for the cathode foils of Examples 1 to 8 and Comparative Examples 1 to 6. In all of Examples 1 to 8, the proportion of metal carbide by XPS is 5% or more, the magnification of the maximum current value by cyclic voltammetry is 6.5 times or more, and the magnification of the half width of the G-band peak by Raman spectroscopy is 3.8 times or more, so that the ESRs at the initial stage and after 2000 hours of deterioration are lower than those of the comparative examples, as described above. In Comparative Example 1, the proportion of metal carbide by XPS and the magnification of the half width of the G-band peak by Raman spectroscopy are the same as those of Examples 1 to 8, but the magnification of the maximum current value by cyclic voltammetry is only 4.5 times, whereas it should be 6.5 times or more. Therefore, the electrochemical effective surface area considering the ease of electric flow is insufficient, and the ESR reduction effect by improving the retention of the solid electrolyte and the electrolyte solution is not achieved, and both the initial ESR and the ESR after 2000 hours of deterioration are high. Comparative Example 2 uses an etched substrate instead of a smooth substrate. Therefore, the substrate surface (especially the inner wall of the etching pit) cannot be entirely covered during film formation, and is partially exposed, resulting in a high ESR after 2000 hours of deterioration. Comparative Example 3 does not have a carbon conductive layer, and the proportion of metal carbides by XPS is 0%, and no mixed layer is formed. Therefore, the first conductive layer containing metal and / or metal compound comes into direct contact with the solid electrolyte, increasing the interface resistance, and both the initial ESR and the ESR after 2000 hours of deterioration are high. Comparative Example 4 has the same proportion of metal carbides by XPS and the magnification of the half width of the G band peak by Raman spectroscopy as Examples 1 to 8, but the magnification of the maximum current value by the cyclic voltammetry method is only 6.0 times, which is required to be 6.5 times or more. Therefore, the electrochemical effective surface area considering the ease of electric flow is insufficient, and the ESR reduction effect by improving the retention of the solid electrolyte and the electrolyte solution is not exerted, and the ESR after 2000 hours of deterioration is high. In Comparative Example 5, the magnification of the maximum current value by the cyclic voltammetry method and the magnification of the half width of the G band peak by Raman spectroscopy are the same as in Examples 1 to 8, but the proportion of metal carbides by XPS is only 3%, whereas it should be 5% or more.Therefore, the ESR reduction effect cannot be achieved, and the ESR after 2000 hours of degradation is high. In Comparative Example 6, the magnification of the maximum current value by cyclic voltammetry and the proportion of metal carbide by XPS are the same as those in Examples 1 to 8, but the magnification of the half-width of the G-band peak by Raman spectroscopy is only 3.5 times, whereas it should be 3.8 times or more. Therefore, the degree of amorphousness of the carbon is low, and the degradation resistance is insufficient, and the ESR after 2000 hours of degradation is high.

[0068] 32 shows the ratio (surface expansion ratio) of the BET specific surface area to the smooth substrate by the Kr adsorption method and the ESR after 2000 hours of degradation for the cathode foils of Examples 1 to 8. Examples 1 to 6 and 8, which have a surface expansion ratio of 1.5 times or more, had a lower ESR after 2000 hours of degradation than Example 7, which has a surface expansion ratio of 1.4 times. Therefore, the ratio (surface expansion ratio) of the BET specific surface area to the smooth substrate by the Kr adsorption method is preferably 1.5 times or more.

[0069] 28 shows the average diameter of the convex portions of the uneven portion on the surface side of the inorganic conductive layer after the carbon conductive layer is applied and the ESR after 2000 hours of degradation in the cathode foils of Examples 1 to 6 and 8. The ESR after 2000 hours of degradation was lower in Examples 1 to 6, in which the average diameter was 210 nm or less, than in Example 8, in which the average diameter was 230 nm. Therefore, since the retention of the solid electrolyte and the electrolytic solution is high and the characteristics after 2000 hours of degradation are excellent, it is more preferable that the ratio of the BET specific surface area by the Kr adsorption method to the smooth substrate is 1.5 times or more, and that the average diameter of the convex portions of the uneven portion on the surface side of the inorganic conductive layer after the carbon conductive layer is applied is 210 nm or less.

[0070] The following are each related to an ultrathin section sample in the thickness direction of the entire coating portion including the substrate portion close to the coating. Fig. 19 shows the element profile distribution obtained by TEM-EDS (transmission electron microscopy-energy dispersive X-ray analysis) of the same cathode foil (Example 2) as in Fig. 6, and Fig. 20 shows the element profile distribution obtained by TEM-EDS of the same cathode foil (Example 4) as in Fig. 7. Fig. 21 shows the element profile distribution obtained by STEM-EELS (scanning transmission electron microscopy-electron energy loss spectroscopy) of the same cathode foil (Example 2) as in Fig. 6 (closer to the carbon conductive layer than Fig. 22), and Fig. 22 shows the element profile distribution obtained by STEM-EELS of the same cathode foil (Example 2) as in Fig. 6 (closer to the substrate than Fig. 21). Fig. 23 shows an element profile distribution (closer to the carbon conductive layer than Fig. 24) obtained by STEM-EELS for the same cathode foil (Example 4) as in Fig. 7, and Fig. 24 shows an element profile distribution (closer to the substrate than Fig. 23) obtained by STEM-EELS for the same cathode foil (Example 4) as in Fig. 7. Here, in Figs. 19 to 24, K indicates the K-shell of electron shells, and in Figs. 20 to 23, L indicates the L-shell of electron shells. It can be seen that in both Examples 2 and 4, a mixed layer exists under the carbon conductive layer.

[0071] Performance test of the solid electrolytic capacitor of the present invention In addition, using the cathode foils of Examples 1 to 8 and Comparative Examples 1 to 6 described above, solid electrolytic capacitors of Examples 1 to 8 and Comparative Examples 1 to 6 were fabricated, respectively (compared to the fabrication method of the hybrid capacitors of Examples 1 to 8 and Comparative Examples 1 to 6, the only difference being that no process of impregnating the capacitor element with an electrolytic solution was performed after the solid electrolyte layer was formed). Performance tests (ESR measurements) were performed on each of the fabricated solid electrolytic capacitors.

[0072] 18 is a table showing the results of ESR measurements performed on the solid electrolytic capacitors of Examples 1 to 8 and the solid electrolytic capacitors of Comparative Examples 1 to 6. In the initial state, the ESR of the solid electrolytic capacitors of Examples 1 to 8 is lower than the ESR of the solid electrolytic capacitors of Comparative Examples 1, 3, 4 and 6.

[0073] Evaluation of physical properties of the electrode material of the present invention The adhesion mechanism between the solid electrolyte and the cathode foil is an adhesive tape type, and FIG. 25 shows comparative data on the degree of adhesion using industrial adhesive tape. A 10 mm wide polypropylene adhesive tape manufactured by Nitto Denko Corporation was used as the adhesive tape, which was cut into a length of 15 cm and placed lightly parallel to the length on a test piece cut into a width of 50 mm and a length of 200 mm, and a press roller with a load of 20 N was moved back and forth once over a length of 100 mm or more on the tape to bond it with a uniform load. One end of the sample piece was firmly held with a clamp, and the tape on the opposite side to the side bonded to the sample piece was folded back 180° near the clamp, and the end was fixed with a clip connected to a push-pull gauge, pulled at a constant speed of 10 mm / sec, and the average value of the tensile load (gf / cm) when the tape peeled off was read, and this value was taken as the degree of tape adhesion. For Examples 1, 2, 4, and 5, reflecting the anchor adhesion effect due to the uneven structure given to the surface layer side, a significantly stronger tape adhesion was obtained than for Comparative Example 1, which did not have an uneven structure given to the surface layer side. In other words, it was found that the uneven structure provided on the surface side of the first conductive layer can have the effect of improving adhesion to the solid electrolyte.

[0074] In recent hybrid capacitors, in order to achieve heat resistance, electrical conductivity, voltage resistance, and manufacturing costs, etc., a solid electrolyte layer is often formed by immersing and impregnating the capacitor in a PEDOT / PSS aqueous dispersion solution, which is made by mixing polyethylenedioxythiophene (PEDOT) with polystyrene sulfonate (PSS) to disperse the PEDOT in an aqueous solution, and then drying the capacitor. The adhesion and retention of the solid electrolyte are thought to depend on the wettability and surface free energy of the cathode foil. Figure 26 shows the contact angles (°) for water, a highly polar solvent, and diiodomethane (methylene iodide, CH2I2), a less polar solvent, and the surface free energy (mJ / m) calculated from these angles using the Owens and Wendt model. 2) (polar hydrogen bonding component and non-polar dispersion force component). The polar hydrogen bonding component is related to the affinity with the water solvent, and the non-polar dispersion force component is related to the affinity with hydrocarbons, organic solvents, polymers, etc. A 1 μL droplet of each solvent, water and diiodomethane, was dropped onto a horizontally placed sample piece, and the contact angle of the droplet after 60 seconds was measured using a contact angle meter (DM-501Hi) manufactured by Kyowa Interface Science Co., Ltd. For Examples 2 and 4, the uneven structure provided on the surface side resulted in a significantly lower contact angle (excellent wettability) with both solvents and a well-balanced high surface free energy value with both components, compared to Comparative Example 1, which did not have an uneven structure provided on the surface side.

[0075] In a wound element in which a capacitor element is made by sandwiching a separator paper between rectangular electrode foil pieces on the anode and cathode sides and winding them, there is a risk of problems with winding misalignment, especially in the type in which winding is started by sandwiching the cathode foil with the winding shaft. This is because if the coefficient of friction between the cathode foil near the winding shaft and the separator paper in contact with it is small, when the winding shaft is pulled out after the wound element is formed, the grip force (friction force) between the cathode foil and the separator paper is insufficient, and the cathode foil in contact with the winding shaft moves in the direction of the winding shaft being pulled out.

[0076] Figure 30 shows the comparative data of the friction coefficient with separator paper. The separator paper used was a 40μm thick separator paper (RTZ3040) made by Nippon Kodoshi Co., Ltd., whose main component is natural cellulose. This was attached to the back (the side that contacts the foil sample) of a flat SUS plate slider (projected dimensions: 63mm square) with a mass of 200g, which was connected to a load cell by a flexible SUS wire via a shock-absorbing spring, and slid horizontally at a constant speed of 100mm / min on the foil sample fixed flat on a smooth acrylic plate with a thickness of 10mm placed horizontally, and the load at that time was sampled every 60 milliseconds. The maximum load generated immediately after the slider started to move was taken as the maximum static friction force, and the average load in a stable motion state was taken as the average kinetic friction force. The static friction coefficient and the average kinetic friction coefficient were obtained by dividing each by the normal force (1.96N) of the slider. For Examples 2, 4, and 5, it was confirmed that the uneven structure provided on the surface side of the first conductive layer improved frictional force, and both the static and dynamic friction coefficients with the separator paper were significantly increased compared to Comparative Example 1, in which no uneven structure was provided on the surface side. In other words, it was found that the uneven structure provided on the surface side of the first conductive layer had the effect of improving adhesion with the solid electrolyte, and could provide a geometric structure suitable for holding the solid electrolyte and the electrolytic solution, while also providing a geometric structure suitable for preventing winding slippage.

[0077] [Note] The present disclosure discloses the following configuration. [Configuration 1] An oxide layer is provided on a smooth substrate, and an inorganic conductive layer is provided on the oxide layer; the inorganic conductive layer has a first conductive layer containing a metal and / or a metal compound and a second conductive layer containing carbon; the first conductive layer has an uneven portion on its surface side, the second conductive layer is located on the outermost layer of the inorganic conductive layer, a mixed layer is formed between the first conductive layer and the second conductive layer, the mixed layer being made of a mixture of a material constituting the first conductive layer and a material constituting the second conductive layer; The composition of the mixed layer is configured to change from a composition containing substantially only the material constituting the first conductive layer to a composition containing substantially only the material constituting the second conductive layer from the first conductive layer to the second conductive layer. An electrode material, when the abundance of each C bonding state is analyzed in a depth direction from a surface layer of the second conductive layer by XPS (X-ray photoelectron spectroscopy), the ratio of the abundance of bonds between atoms of metal elements constituting the first conductive layer and carbon atoms to the total abundance of each C bonding state in a C1s spectrum is 5% or more, the maximum current value of a cyclic voltammogram obtained by cyclic voltammetry under the conditions of a sweep range of ±0.3 V vs Pt, a sweep rate of 500 mV / sec, an electrolyte temperature of 30° C., a reference electrode of Pt, a counter electrode of stainless steel, and a working electrode made of the above-mentioned electrode material is 6.5 times or more of the maximum current value of a cyclic voltammogram obtained under the above-mentioned conditions when the working electrode is made of the above-mentioned smooth substrate, Regarding the half-width of a G-band peak obtained by peak separation in a Raman spectrum by Raman spectroscopy, the half-width of the carbon contained in the second conductive layer is 3.8 times or more larger than the half-width of a graphite crystal. electrode material. [Configuration 2] 2. The electrode material according to claim 1, wherein the first conductive layer and the second conductive layer are made of different materials. [Configuration 3] 3. The electrode material according to claim 1 or 2, wherein the smooth substrate and the first conductive layer are made of different materials. [Configuration 4] 4. The electrode material according to any one of configurations 1 to 3, wherein the second conductive layer is made substantially of carbon. [Configuration 5] 5. The electrode material according to any one of configurations 1 to 4, wherein the inorganic conductive layer further has a dense layer in which the metal and / or metal compound is densely present, and the dense layer is formed between the oxide layer and the first conductive layer. [Configuration 6] The electrode material according to any one of configurations 1 to 5, wherein both the first conductive layer and the second conductive layer, or at least the first conductive layer, of the inorganic conductive layer is made of a particle deposition layer, and the first conductive layer contains at least one of titanium, aluminum, and nitrides, oxides, oxynitrides, carbides, and carbonitrides thereof. [Configuration 7] 7. The electrode material according to any one of configurations 1 to 6, wherein the oxide layer is an oxide layer containing phosphorus. [Configuration 8] 8. The electrode material according to any one of configurations 1 to 7, wherein the smooth substrate comprises aluminum or an aluminum alloy. [Configuration 9] 9. The electrode material according to any one of configurations 1 to 8, wherein the carbon is graphite-like carbon. [Configuration 10] 10. The electrode material according to any one of configurations 1 to 9, wherein a BET specific surface area using krypton (Kr) as an adsorption gas is 1.5 times or more the BET specific surface area of ​​the smooth substrate. [Configuration 11] 10. The electrode material according to any one of configurations 1 to 9, wherein a BET specific surface area using krypton (Kr) as an adsorption gas is 1.5 times or more the BET specific surface area of ​​the smooth substrate, and an average diameter of convex portions of the concave-convex portion on the surface side of the inorganic conductive layer is 210 nm or less. [Configuration 12] 12. An electrode material according to any one of configurations 1 to 11, wherein the static friction coefficient and kinetic friction coefficient of the surface on the surface side against a separator paper are higher than the static friction coefficient and kinetic friction coefficient of the surface on the surface side against a separator paper of an electrode material having a conductive layer that is an outermost layer on the surface side and is made of carbon on a smooth base material and has no uneven portion on the surface side. [Configuration 13] 13. A cathode foil for an electrolytic capacitor, comprising an anode foil and a cathode foil, and at least a solid electrolyte interposed between the anode foil and the cathode foil, the cathode foil using the electrode material according to any one of configurations 1 to 12. [Configuration 14] 14. An electrolytic capacitor having at least a solid electrolyte interposed between an anode foil and a cathode foil, the electrolytic capacitor having the cathode foil according to configuration 13. [Configuration 15] 15. The electrolytic capacitor of claim 14, further comprising an electrolyte between the anode foil and the cathode foil. [Industrial Applicability]

[0078] The electrode material of the present invention can be used as a cathode foil for electrolytic capacitors such as hybrid capacitors, solid electrolytic capacitors, etc. Furthermore, the electrode material of the present invention can be used in various capacitors, various power storage devices such as electric double layer capacitors, lithium ion capacitors, and lithium ion batteries, and various power generation elements such as fuel cells, solar cells, thermoelectric power generation elements, and vibration power generation elements. [Explanation of symbols]

[0079] 1 Cathode foil (electrode material) 2 Base material 3. Oxide layer 4 First Conductive Layer 5 Second Conductive Layer 6 Layer compacta 7 Mixed Layer 8 Wound type solid electrolytic capacitors, Wound type hybrid capacitors 9 Anode foil 10 Cathode foil 11 Separator paper 12 Capacitor element 13 Anode terminal 14 Cathode terminal 15 Aluminum case 16 Sealing rubber

Claims

1. An oxide layer is provided on a smooth substrate, and an inorganic conductive layer is provided on the oxide layer; the inorganic conductive layer has a first conductive layer containing a metal and / or a metal compound and a second conductive layer containing carbon; the first conductive layer has an uneven portion on a surface side thereof, the second conductive layer is located on the outermost layer of the inorganic conductive layer, a mixed layer is formed between the first conductive layer and the second conductive layer, the mixed layer being made of a mixture of a material constituting the first conductive layer and a material constituting the second conductive layer; The composition of the mixed layer is configured to change from a composition containing substantially only the material constituting the first conductive layer to a composition containing substantially only the material constituting the second conductive layer from the first conductive layer to the second conductive layer. An electrode material, when the abundance of each C bonding state is analyzed in a depth direction from a surface layer of the second conductive layer by XPS (X-ray photoelectron spectroscopy), the ratio of the abundance of bonds between atoms of metal elements constituting the first conductive layer and carbon atoms to the total abundance of each C bonding state as determined by a C1s spectrum is 5% or more, the maximum current value of a cyclic voltammogram obtained by cyclic voltammetry under the conditions of a sweep range of ±0.3 V vs Pt, a sweep rate of 500 mV / sec, an electrolyte of 30° C., a Pt reference electrode, a stainless steel counter electrode, and a working electrode made of the above-mentioned electrode material is 6.5 times or more of the maximum current value of a cyclic voltammogram obtained under the above-mentioned conditions when the working electrode is made of the above-mentioned smooth substrate, Regarding the half-width of a G-band peak obtained by peak separation in a Raman spectrum by Raman spectroscopy, the half-width of the carbon contained in the second conductive layer is 3.8 times or more larger than the half-width of a graphite crystal. electrode material.

2. The electrode material according to claim 1 , wherein a material constituting the first conductive layer and a material constituting the second conductive layer are different from each other.

3. The electrode material according to claim 1 or 2, wherein the smooth substrate and the first conductive layer are made of different materials.

4. The electrode material according to claim 1 or 2, wherein the second conductive layer consists essentially of carbon.

5. 3. The electrode material according to claim 1, wherein the inorganic conductive layer further comprises a dense layer in which the metal and / or metal compound is densely present, the dense layer being formed between the oxide layer and the first conductive layer.

6. 3. The electrode material according to claim 1 or 2, wherein both the first conductive layer and the second conductive layer, or at least the first conductive layer, of the inorganic conductive layers are made of a particle deposition layer, and the first conductive layer contains at least one of titanium, aluminum, and nitrides, oxides, oxynitrides, carbides, and carbonitrides thereof.

7. The electrode material according to claim 1 or 2, wherein the oxide layer is an oxide layer containing phosphorus.

8. The electrode material according to claim 1 or 2, wherein the smooth substrate comprises aluminum or an aluminum alloy.

9. The electrode material according to claim 1 or 2, wherein the carbon is graphite-like carbon.

10. 3. The electrode material according to claim 1, wherein a BET specific surface area using krypton (Kr) as an adsorption gas is 1.5 times or more the BET specific surface area of ​​the smooth substrate.

11. 3. The electrode material according to claim 1, wherein a BET specific surface area using krypton (Kr) as an adsorption gas is 1.5 times or more the BET specific surface area of ​​the smooth substrate, and an average diameter of convex portions of the uneven portion on the surface side of the inorganic conductive layer is 210 nm or less.

12. 3. The electrode material according to claim 1 or 2, wherein the static friction coefficient and dynamic friction coefficient of the surface on the surface side against a separator paper are higher than the static friction coefficient and dynamic friction coefficient of the surface on the surface side against a separator paper of an electrode material having a conductive layer that is the outermost layer on the surface side and is made of carbon on a smooth base material and having no uneven portion on the surface side.

13. 3. A cathode foil for an electrolytic capacitor, comprising an anode foil and a cathode foil, at least a solid electrolyte being interposed between the anode foil and the cathode foil, the cathode foil using the electrode material according to claim 1 or 2.

14. An electrolytic capacitor having at least a solid electrolyte interposed between an anode foil and a cathode foil, the electrolytic capacitor comprising the cathode foil according to claim 13.

15. 15. The electrolytic capacitor according to claim 14, further comprising an electrolyte interposed between the anode foil and the cathode foil.

Citation Information

Patent Citations

  • Electrode foil for solid electrolytic capacitor

    JP2012174865A

  • Cathode foil for aluminum electrolytic capacitor

    JP2014022707A

  • Electrolytic capacitor and manufacturing method thereof

    JP2019179884A

  • Electrode foil, current collector, electrode, and energy storage element using same

    WO2012115050A1

  • Electrode body, electrolytic capacitor provided with electrode body, and method for producing electrode body

    EP3817020A1

Cited By

  • Aluminum electrolytic capacitor for zero-power-consumption fast-charging power source and preparation method of aluminum electrolytic capacitor

    CN121460387A